Knowledge of laryngopharyngeal reflux disease among otolaryngologists in 3A hospitals in Beijing. Issue 3 (October 2020) - Zhang, Junbo; Xiao, Shuifang; Du, Xiaowan; Zhao, Xin; Jia, Junxiao
Objective: This study aimed to evaluate knowledge of laryngopharyngeal reflux disease (LPRD) among otolaryngologists in 3A hospitals in Beijing. Methods: A cross-sectional questionnaire survey of LPRD knowledge was conducted with otolaryngologists in 40 3A hospitals in Beijing. A response rate of <80% was obtained from one hospital, so data from 331 valid questionnaires from the other 39 hospitals were analysed. Results: The most common source of LPRD knowledge was academic lectures (80.1%). The most commonly known risk factors, symptoms, clinical signs and associated diseases were unhealthy eating habits (49.2%), foreign body sensation in the pharynx (71.0%), hyperaemia (42.3%) and pharyngolaryngitis (63.7%), respectively. Only 57.7% of otolaryngologists knew about 24-hour pH monitoring as a gold standard diagnostic test for LPRD. The most commonly known treatment option was medication (93.1%). Most physicians (86.7%) had made a clinical diagnosis of LPRD; however, only 59.9% of them had followed up the treatment outcomes. The most common treatment provided was medication (82.6%). Conclusions: Knowledge of LPRD among otolaryngologists in 3A hospitals in Beijing was insufficient. Educational programs are needed to increase the knowledge of LPRD among otolaryngologists.